Using Transcript Levels of Nitrate Transporter 2 as Molecular Indicators to Estimate the Potentials of Nitrate Transport in Symbiodinium, Cladocopium, and Durusdinium of the Fluted Giant Clam, Tridacna squamosa - Pang, Caryn Z.; Ip, Yuen K.; Chew, Shit F. (Frontiers in Marine Science, 2021)
Giant clams are important ecosystem engineers of coral reefs because they harbor large quantities of phototrophic Symbiodiniaceae dinoflagellates of mainly genera Symbiodinium, Cladocopium, and Durusdinium. The coccoid dinoflagellates donate photosynthate and amino acids to the clam host, which in return needs to supply inorganic carbon and nitrogen to them. The host can conduct light-enhanced absorption of nitrate (NO3–), which can only be metabolized by the symbionts. This study aimed to clone nitrate transporter 2 (NRT2) from the symbionts of the fluted giant clam, Tridacna squamosa. Here, we report three major sequences of NRT2 derived from Symbiodinium (Symb-NRT2), Cladocopium (Clad-NRT2) and Durusdinium (Duru-NRT2). Phenogramic analysis and molecular characterization confirmed that these three sequences were NRT2s derived from dinoflagellates. Immunofluorescence microscopy localized NRT2 at the plasma membrane and cytoplasmic vesicles of the symbiotic dinoflagellates, indicating that it could partake in the uptake and transport of NO3–. Therefore, the transcript levels of Symb-NRT2, Clad-NRT2, and Duru-NRT2 could be used as molecular indicators to estimate the potential of NO3– transport in five organs of 13 T. squamosa individuals. The transcript levels of form II ribulose-1, 5-bisphosphate carboxylase/oxygenase (rbcII) of Symbiodinium (Symb-rbcII), Cladocopium (Clad-rbcII) and Durusdinium (Duru-rbcII) were also determined in order to calculate the transcript ratios of Symb-NRT2/Symb-rbcII, Clad-NRT2/Clad-rbcII, and Duru-NRT2/Duru-rbcII. These ratios expressed the potentials of NO3– transport with reference to the phototrophic potentials in a certain genus of coccoid dinoflagellate independent of its quantity. Results obtained indicate that Symbiodinium generally had a higher potential of NO3– transport than Cladocopium and Durusdinium at the genus level. Furthermore, some phylotypes (species) of Symbiodinium, particularly those in the colorful outer mantle, had very high Symb-NRT2/Symb-rbcII ratio (7–13), indicating that they specialized in NO3– uptake and nitrogen metabolism. Overall, our results indicate for the first time that different phylotypes of Symbiodiniaceae dinoflagellates could have dissimilar abilities to absorb and assimilate NO3–, alluding to their functional diversity at the genus and species levels.